2015
DOI: 10.1038/ncomms8722
|View full text |Cite
|
Sign up to set email alerts
|

The key role of the scaffold on the efficiency of dendrimer nanodrugs

Abstract: Dendrimers are well-defined macromolecules whose highly branched structure is reminiscent of many natural structures, such as trees, dendritic cells, neurons or the networks of kidneys and lungs. Nature has privileged such branched structures for increasing the efficiency of exchanges with the external medium; thus, the whole structure is of pivotal importance for these natural networks. On the contrary, it is generally believed that the properties of dendrimers are essentially related to their terminal groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 42 publications
0
112
0
Order By: Relevance
“…19) was used to decipher the biological processes leading to the anticancer properties. It was shown that the first step is the anti-inflammatory activation of monocytes, which is particularly important against chronic inflammatory diseases [83,84]. In second time, a cross-talk between monocytes and NK cells induces the proliferation of the latter, including with blood from patients suffering of multiple myeloma disease [85].…”
Section: Optical Imagingmentioning
confidence: 99%
“…19) was used to decipher the biological processes leading to the anticancer properties. It was shown that the first step is the anti-inflammatory activation of monocytes, which is particularly important against chronic inflammatory diseases [83,84]. In second time, a cross-talk between monocytes and NK cells induces the proliferation of the latter, including with blood from patients suffering of multiple myeloma disease [85].…”
Section: Optical Imagingmentioning
confidence: 99%
“…Indeed, as shown in Fig. 5, molecular modeling of one of the relaxed conformers of dendrimer 5 (G1-30 NH 2 ), wherein two of the amine pairs can span over a distance of 52 Å may account for the dendrimer's conformational adaptation 62 to better reach the anionic phosphate groups on plasmid DNA and siRNA. The above data confirm that polycationic pegylated dendrimers of low generation (G1 here) hold great promise as nanocarriers for gene transfection.…”
Section: Discussionmentioning
confidence: 99%
“…25,34 The starburst PAMAM dendrimers used today have an ethylenediamine core based on the reports of Tomalia et al 16 25,34 The starburst PAMAM dendrimers used today have an ethylenediamine core based on the reports of Tomalia et al 16 …”
Section: Synthesis and Properties Of Dendrimermentioning
confidence: 99%